1994
DOI: 10.1002/1097-0142(19940415)73:8<2119::aid-cncr2820730817>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histologic involvement of regional lymph nodes in malignant melanoma. Adjuvant vindesine improves survival

Abstract: Background. This report is a study of prognostic factors, including adjuvant chemotherapy, that influence survival of patients with malignant melanoma who have clinical and pathologic involvement of regional lymph nodes. Methods. A total of 169 evaluable patients with malignant melanoma metastatic to regional lymph nodes were registered consecutively and prospectively between June 1977 and December 1986 in the computerized data base of the melanoma registry at Westminster Hospital. Eighty‐seven of these patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
3
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 29 publications
0
10
3
2
Order By: Relevance
“…Unlike a prior retrospective trial [358], this analysis demonstrated no significant differences neither in recurrence-free nor in overall survival. Thus, no adjuvant chemotherapy has until now been proven to be beneficial.…”
Section: Level Of Evidence 1acontrasting
confidence: 85%
“…Unlike a prior retrospective trial [358], this analysis demonstrated no significant differences neither in recurrence-free nor in overall survival. Thus, no adjuvant chemotherapy has until now been proven to be beneficial.…”
Section: Level Of Evidence 1acontrasting
confidence: 85%
“…Sample size calculation was performed according to published data by Retsas et al [12] assuming a 3-year survival rate of 25% for patients in the observation group and 40% in the treatment group. Sixty-three patients were required in each group to achieve 80% power to detect this 25% increase in overall survival after 4 years, assuming a P-value of 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Back in 1994, Retsas and colleagues [12] reported about a significant benefit in 5-year overall survival after complete lymph node dissection in patients treated with vindesine. This trial, however, did not have a randomized design and the analysis was based on historical control patients.…”
Section: Introductionmentioning
confidence: 99%
“…Im Jahre 1994 wurde von Retsas et al eine nicht randomisierte Studie zur adjuvanten Therapie nach tastbaren Lymphknotenmetastasen publiziert, wobei das Vinca-Alkaloid Vindesine über 2 Jahre zur Anwendung kam [30]. Die 5-Jahres-Überlebensrate von 87 Patienten mit adjuvanter Vindesine-Therapie war mit 49% signifikant besser als die Überlebensrate von 28% für die 82 Patienten der Kontrollgruppe.…”
Section: Diskussion Studienvergleichunclassified
“…30% dieser Subpopulation nach einem Intervall von bis zu 20 Jahren tastbare Lymphknotenmetastasen, wobei 2/3 der Absiedlungen in den ersten 2 Jahren nach der Exzision des Primärtumors diagnostiziert werden [7,27,32]. Aufgrund des späteren Diagnosezeitpunktes ("lead time bias"; [28]), möglicherweise auch aufgrund der jetzt deutlich höheren Tumorlast in den Lymphknoten ist die Prognose in der Patientengruppe mit tastbaren Lymphknotenmetastasen offenbar deutlich schlechter (5-Jahres-Überlebens-raten 13%-36%; [17,25,27,29,30,33] …”
unclassified